Trial of antibiotic restraint in presumed pneumonia: A Surgical Infection Society multicenter pilot. Issue 2 (18th February 2023) - Guidry, Christopher A.; Beyene, Robel T.; Watson, Christopher M.; Sawyer, Robert G.; Chollet-Hinton, Lynn; Simpson, Steven Q.; Atchison, Leanne; Derickson, Michael; Cooper, Lindsey C.; Pennington, G. Patton; VandenBerg, Sheri; Halimeh, Bachar N.; et al.
Abstract : In this multicenter, cluster-randomized, crossover trial, a protocol of specimen-initiated antibiotics for suspected ICU-acquired pneumonia did not result in improved outcomes and had similar compliance when compared to an immediate initiation protocol. Abstract : BACKGROUND: Pneumonia is the most common intensive care unit–acquired infection in the trauma and emergency general surgery population. Despite guidelines urging rapid antibiotic use, data supporting immediate antibiotic initiation in cases of suspected infection are limited. Our hypothesis was that a protocol of specimen-initiated antibiotic initiation would have similar compliance and outcomes to an immediate initiation protocol. METHODS: We devised a pragmatic cluster-randomized crossover pilot trial. Four surgical and trauma intensive care units were randomized to either an immediate initiation or specimen-initiated antibiotic protocol for intubated patients with suspected pneumonia and bronchoscopically obtained cultures who did not require vasopressors. In the immediate initiation arm, antibiotics were started immediately after the culture regardless of patient status. In the specimen-initiated arm, antibiotics were delayed until objective Gram stain or culture results suggested infection. Each site participated in both arms after a washout period and crossover. Outcomes were protocol compliance, all-cause 30-day mortality, and ventilator-free alive days at 30 days. Standard statistical techniques were applied. RESULTS: A total of 186 patients had 244 total cultures, of which only the first was analyzed. Ninety-three patients (50%) were enrolled in each arm, and 94.6% were trauma patients (84.4% blunt trauma). The median age was 50.5 years, and 21% of the cohort was female. There were no differences in demographics, comorbidities, sequential organ failure assessment, Acute Physiology and Chronic Health Evaluation II, or Injury Severity Scores. Antibiotics were started significantly later in the specimen-initiated arm (0 vs. 9.3 hours; p < 0.0001) with 19.4% avoiding antibiotics completely for that episode. There were no differences in the rate of protocol adherence, 30-day mortality, or ventilator-free alive days at 30 days. CONCLUSION: In this cluster-randomized crossover trial, we found similar compliance rates between immediate and specimen-initiated antibiotic strategies. Specimen-initiated antibiotic protocol in patients with a suspected hospital-acquired pneumonia did not result in worse clinical outcomes compared with immediate initiation. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level II. Abstract :